Educational activities and learning in the Lebensborn project of Nazi Germany - Milenović Živorad M. (University of Kragujevac - Faculty of Pedagogy, Užice, 2020)
During the time of Nazi Germany from 1933 to 1945, that is, to the end of World War II, the most horrific crimes in human history took place. Nazi Germany was based on militarism, racism, anti-Semitism, ideologism and occultism. First, the Nuremberg Laws were passed, which led to the Holocaust, and on December 12, 1935, in Munich, by the order of the commander of the SS troops, Heinrich Himmler, a secret state Lebensborn project was established. The goal of this state project was to create a pure Aryan race, which was considered a key condition for Germany to become the world's leading power in military, economic and cultural terms, and for the German people to rule the world with their sublime tradition and culture. The Lebensborn project involved the birth of children from biological mothers carefully selected from the ranks of racially pure young, beautiful and healthy German girls and biological fathers from the ranks of SS troops, who would later be housed in Lebensborn homes or in the homes of SS officers or prominent purely Aryan families. Children abducted all over Europe, who met the criteria of seemingly belonging to the members of the pure Aryan race, were also accommodated in these homes. In addition to custody and upbringing, the educational activities and teaching of these children in Lebensborn homes were carried out under strict supervision, based on the principles of fascist pedagogy the point that will be discussed in this theoretical study.